PENGARUH PENERAPAN LAGU-LAGU ANAK ISLAMI PADA KECERDASAN SPIRITUAL ANAK USIA DINI RA DARUNNASYIIN WINONGAN PASURUAN: THE INFLUENCE OF IMPLEMENTING ISLAMIC CHILDREN'S SONGS ON THE SPIRITUAL INTELLIGENCE OF EARLY CHILDHOOD AT RA DARUNNASYIIN WINONGAN PASURUAN - Maulida, Susi (Universitas Islam Malang, 2023)
This research was motivated by the low spiritual intelligence of children in the A RA Darunnasyiin group, this can be seen from the children's low awareness of always connecting with Allah in every situation. Children's spiritual intelligence is less developed, most likely because the methods used to develop spiritual intelligence at RA Darunnasyiin are not appropriate. The aim of this research was to examine the influence of Islamic children's songs on the spiritual intelligence of young children in the A RA Darunnasyiin Winongan Pasuruan group. The research method used is a quantitative method. The type of research used is experimental research (Experimental Research). The form of experimental design used in this research is pre-experimental design. The form of pre-experimental design in this research is one-group pre-test-post-test design. Sampling in this research used a regular method (non-probability sampling) with a saturated sampling technique. The results showed that there was an increase in the scores obtained by children from the pre-test stage to the post-test stage. The total score obtained at the pre-test stage was 250 and all samples totaling 18 children had spiritual intelligence which was in the unskilled category, the total score at the post-test stage increased to 393 and 16 children were in the very well developed category and 2 children were in the developing category as expected. After conducting research, it is known that t0 > tt at the 5% significance level, namely the results obtained t0 = 64.39 and tt = 2.110 (64.39 > 2.110), so the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This shows that there is a significant influence between Islamic children's songs on the spiritual intelligence of early childhood.